2011
DOI: 10.3171/2010.8.jns10520
|View full text |Cite
|
Sign up to set email alerts
|

Defining the “edge of the envelope”: patient selection in treating complex sellar-based neoplasms via transsphenoidal versus open craniotomy

Abstract: Since the reemergence of the transsphenoidal approach as a primary means of accessing and resecting sellar region tumors in the 1960s by Hardy and Guiot, several key advances have improved the ability to safely treat patients with larger and increasingly complex tumors of the anterior and middle skull base. 28,43 In particular, the operating microscope, extended transsphenoidal approaches, advanced neuroimaging, intraoperative neuronavigation, and neuroendoscopy have collectively improved the ability to safely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
110
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 74 publications
0
110
0
5
Order By: Relevance
“…Moreover, several recent papers have tried to outline factors that correlate with higher morbidity to assist the clinician with patient selection. In this paper we examined 2 of these factors, namely the absence of a cortical cuff indicating the proximity of small perforators to the tumor capsule, 26,52 and the presence of brain edema as an indication of brain invasion. 52 Our results in this large series of meningiomas indicate that these factors may not be as important as careful case selection and technical skills that are acquired over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several recent papers have tried to outline factors that correlate with higher morbidity to assist the clinician with patient selection. In this paper we examined 2 of these factors, namely the absence of a cortical cuff indicating the proximity of small perforators to the tumor capsule, 26,52 and the presence of brain edema as an indication of brain invasion. 52 Our results in this large series of meningiomas indicate that these factors may not be as important as careful case selection and technical skills that are acquired over time.…”
Section: Discussionmentioning
confidence: 99%
“…26,52 Fifth, any evidence of edema in the adjacent brain indicates possible brain invasion requiring complex brain dissection and hemostasis techniques not possible with endonasal surgery. 52 While each of these points has merit, they are primarily derived from results achieved in the early years of endonasal surgery before the development of a variety of technical advances that have made these approaches both more effective and safer. Likewise, recommendations regarding appropriate case selection were not clear given the lack of experience and consensus within the endonasal surgical community.…”
mentioning
confidence: 99%
“…The same principles are valid in cases of giant adenomas, where the extended approach has proved to facilitate, in most instances, a wider lesion exposure just after the dural opening over the sellar-suprasellar space, thus avoiding any retraction of neurovascular structures [16][17][18][19]. However, there are conditions that could render more troublesome the transsphenoidal approach, either related to the anatomy of the surgical route or to the inner features of the lesion itself, i.e., the size of the sella, its degree of ossification, the size and the pneumatization of the sphenoid sinus, and/or carotid arteries position and shape [1,6,20,21].On the other hand, transcranial surgery should be preferred when tumors present with extensive intracranial invasion, with asymmetric lateral development, into the anterior cranial fossa or lateral or posterior extension into the middle and posterior cranial fossa, particularly if major vessel involvement is present and/or whether transsphenoidal surgery has been already unsuccessful, and in these regards, several authors have reported surgical strategy and results, properly addressing indications, pros, and cons [22][23][24].When perceiving this controversial scenario, we moved backward through our series and analyzed the decisionmaking process, i.e., surgical approach choice, in those special-featured adenomas (giant, asymmetric, dumb-bell shaped). Although it is not possible to define a unique paradigm of management, we could thread a common line of attitude we have been relying on.…”
mentioning
confidence: 99%
“…The same principles are valid in cases of giant adenomas, where the extended approach has proved to facilitate, in most instances, a wider lesion exposure just after the dural opening over the sellar-suprasellar space, thus avoiding any retraction of neurovascular structures [16][17][18][19]. However, there are conditions that could render more troublesome the transsphenoidal approach, either related to the anatomy of the surgical route or to the inner features of the lesion itself, i.e., the size of the sella, its degree of ossification, the size and the pneumatization of the sphenoid sinus, and/or carotid arteries position and shape [1,6,20,21].…”
mentioning
confidence: 99%
“…However, there are also comprehensive surgical modifications that permit access and provide effective initial management of giant PAs with favorable results [22]. There are certain features that favor the transcranial open craniotomy over the trans-sphenoidal route, specifically, significant supraor retrosellar or lateral extensions of the tumor, brain invasion with edema, firm tumor consistency, involvement or vasospasm of the arteries of the circle of Willis, and encasement of the optic apparatus or invasion of the optic foramina [23]. In this study, almost half of patients had extensive tumors and one-third had cavernous sinus invasion.…”
Section: Surgical Managementmentioning
confidence: 99%